2016
DOI: 10.1007/s00198-016-3672-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of doxorubicin administration on bone strength and quality in sedentary and physically active Wistar rats

Abstract: DOX negatively affects bone geometry, trabecular microarchitecture, and femur mechanical properties in growing Wistar rats. Exercise further aggravates the detrimental effects of past DOX treatment on bone mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Indeed, Fonseca et al . previously reported that anti-cancer drugs, such as doxorubicin, routinely used in pediatric cancer treatment, not only promote muscle wasting 35 , but also negatively affects the overall bone morphology, as well as the femur mechanical properties in rats 74 . This is of particular importance, especially considering that patients affected with metastatic colorectal cancer usually undergo multiple rounds of chemotherapy treatment, thereby having far more chances to develop such toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Fonseca et al . previously reported that anti-cancer drugs, such as doxorubicin, routinely used in pediatric cancer treatment, not only promote muscle wasting 35 , but also negatively affects the overall bone morphology, as well as the femur mechanical properties in rats 74 . This is of particular importance, especially considering that patients affected with metastatic colorectal cancer usually undergo multiple rounds of chemotherapy treatment, thereby having far more chances to develop such toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical report indicated that premenopausal breast cancer patients treated with AC combination resulted in a lower bone mineral density and significant bone loss [ 18 ]. Animal studies have also reported that adriamycin exposure caused a reduction in bone formation due to reduced osteoblast differentiation [ 19 ], and can negatively affect bone trabecular microarchitecture and mechanical properties [ 20 ]. Using a rat AC treatment model mimicking the clinical setting, our recent animal study also revealed that 4 cycles of AC treatment were able to cause severe bone marrow damage and some reduction in trabecular bone volume [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient did not reach the average Swedish height, but body growth was harmonic. We can hypothesize that chemotherapy treatment with Vinkristin, Ifofosfamid, Etoposid and especially Doxorubicin affected the patient's overall growth (Fonseca et al, ).…”
Section: Discussionmentioning
confidence: 99%